An investigation into indoor air quality and sick building syndrome - Hosseinia, Hamid Reza; Mohd Yunos, Mohd Yazid; Ismail, Sumarni; Mohd. Yaman, Maheran (American Scientific Publishers, 2017)
This study focuses on indoor air quality and its influence to the healthy of the occupiers and in this case study identified the dissatisfaction level among the respondents in the education environments. Air velocity, temperature, and relation humidity were investigated using a device and then the analysis is correlate with the satisfaction level of the respondents. Using the analysis of regression, the impact of these three items on the dissatisfaction of students, staff, and lecturer were estimated. It is known that temperature and wind speed have the greatest impact on dissatisfaction level. The study also identified the sick building syndrome among the raspondents namely among students, staffs, and lecturers which found that medium risk of sick building syndrome were found between the respondents. The study identified that the sick buildings symptoms tended to disappear after the participants leave their office, classroom and the buildings.